Chemical Composition and Antibacterial Activity of the Essential Oil of Allium jesdianum Boiss. & Buhse From Iran - H Amiri (Institue of Medicinal Plants, ACECR, 2007)
Background: Allium jesdianum Boiss. belongs to Liliaceae family, which grows widly in west and northwest of Iran and has nutritive and medicine uses in the regions.   Objective: Identification of chemical composition and antibacterial activity of the essential oil and different extracts of Allium jesdianum.   Methods: The aerial parts were collected in flowering stage. The essentail oil from aerial parts, which was obtained by Hydrodistillation, was subjected to GC and GC/MS. The antibacterial effects of essential oil and aqueous, methanolic and ethanolic extracts of Allium jesdianum were studied by digging hole and measuring diameter of grows inhibiting ring and Gentamicine antibiotic was used for comparison.   Results: The yield of essential oil obtained by hydrodistillation from dried plant material was 0.1% w/w. The major components were found to be: Trisulfide dimethyl (22.34%), Hexadecanoic acid (19.03%), Phytol (12.82%), Disulfide methyl-1-(methylthio) ethyl (9.25%), Pentacosane (8.03%), Curzerene (7.62%). The study of antibacterial activity showed that the ethanolic extracts have stronger antibacterial effects compared with essential oil and other extracts. Discussion: In conclusion, the data reported in our study showed that the sulfide compounds represented the most abundant compounds as the other Allium species. The antibacterial activity of oil and extracts of A. jesdianum can be attributed of sulfide and terpenoides compounds.